THE ARCHEOLOGY OF ECUADORIAN DEMOCRACY IN THE OPINION SPEECH - Albornoz Tinajero, Consuelo de las Mercedes (Revista de Historia Social y de las Mentalidades, 2022)
This article examines the opinion discourse on democracy published in the Ecuadorian written press between 1968 and 1979, at a time when Ecuador experienced institutional political instability. In this period there was a recovery of democracy, and the assumption of a president elected by popular vote; the coup of the same president; the replacement of him by a military government and the subsequent replacement by a triumvirate. This board began the process of legal restructuring in 1976 that culminated in the re-institutionalization of democratic life in 1979.
Keywords: Archaeological Analysis of Discourse; Opinion Speech; Democratic Restoration; Ecuador